The Result Soft and Hard Skills Assessment on Vocational Skills of Children with Mild Intellectual Disabilities at The Liwet Instant Company 1001 Garut - Annisi, Mughi Puspa; Aprilia, Imas Diana; Homdijah, Oom Sitti (Department of Special Education, 2023)
In preparing graduate children with mild intelligence barriers who are ready to work, of course, it requires an initial description of the child's condition in vocational skills in the aspects of soft skills and hard skills according to the demands of the world of work that are targeted, teachers can do this through an assessment process. This research method uses the mixed method method. The purpose of this study was to determine the child's profile, including a description of the child's potential, barriers and needs. The results of this study included child profile data which were processed using quantitative data and qualitative data on 5 aspects of soft skills, 2 basic development and 7 aspects of hard skills. The results of the assessment showed that there were aspects of soft skills that still needed to be optimized in interpersonal behavior with a score of 56%, while in the hard skills aspect there were aspects of milled rice processing with a score of 55% which still needed to be optimized as well as skills, especially skills in weighing rice. The results of this assessment were used as the basis for creating a work readiness vocational program at the Garut 1001 Instant Liwet Rice Company.